2006
DOI: 10.1186/1479-5876-4-34
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin in Chronic Fatigue Syndrome (CFS), an analysis of clinical data

Abstract: BackgroundCFS is a clinical state with defined symptoms, but undefined cause. The patients may show a chronic state of immune activation and treatment with an antibiotic in this subgroup has been suggested.MethodsIn a retrospective study, the response of CFS patients to azithromycin, an antibiotic and immunomodulating drug, has been scored from the patients records and compared with clinical and laboratory data. Azithromycin was not the first choice therapy, but offered when the effect of counseling and L-carn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Azithromycin is an antibiotic with a wide range of imunomodulatory effects [ 19 , 20 , 21 ] used in the treatment of number of bacterial infections, due to inhibition of the generation of.…”
Section: Resultsmentioning
confidence: 99%
“…Azithromycin is an antibiotic with a wide range of imunomodulatory effects [ 19 , 20 , 21 ] used in the treatment of number of bacterial infections, due to inhibition of the generation of.…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study measuring the response of patients with CFS to azithromycin found that 58 of the 99 participants reported a decrease in symptom severity [34]. The responders improved to an estimated maximum of 80% of their premorbid level.…”
Section: Antiviral Treatmentsmentioning
confidence: 96%
“…The commonality and nonspecificity of fatigue, and the observation that antibiotics may improve chronic fatigue in noninfectious or other postinfectious illnesses, raise doubts as to whether it was the elimination of B burgdorferi that resulted in this outcome. 106108 …”
Section: Extended Antibiotics For the Treatment Of Post-lyme Diseasementioning
confidence: 99%